Molecular Phylogeny and Morphology Reveal Four New Species of Conocybe (Bolbitiaceae, Agaricales) from the Qinghai-Xizang Plateau, China - Xi-Xi Han; Dorji Phurbu; Bin Cao; Jia-Xin Li; Xin-Yu Zhu; Lin-Hui Liu; Naritsada Thongklang; Kevin D. Hyde; Rui-Lin Zhao (Journal of Fungi)
The Qinghai-Xizang Plateau, known for its high altitude, geological history of plate collision, crustal uplift, and special ecology factors, provides an ideal environment for studying fungal biodiversity in extreme environmental conditions. Some species within the Conocybe, containing secondary metabolites such as psilocybin, phallotoxins, and amatoxins, have potential medicinal value for treating psychiatric disorders and for use in drug development. This study investigates Conocybe (Bolbitiaceae, Agaricales) on the Plateau, based on specimens collected over the past decade, using morphological and molecular phylogenetic analyses. Seven species were identified, including four new species: C. alticola, C. alticoprophila, C. versicolor, and C. yadongensis. Molecular analyses, utilizing multi-gene sequence data (ITS, nrLSU, and tef-1α), support the taxonomic position of these new species within this genus as new species. Detailed descriptions, illustrations, photographs, line drawings, and comparisons with related species are provided for the new taxa. This study enriches the species diversity of Conocybe on the Qinghai-Tibet Plateau, further enhancing our understanding of fungal biodiversity in this region.